2008
DOI: 10.1038/nm.1871
|View full text |Cite
|
Sign up to set email alerts
|

Divergent TLR7 and TLR9 signaling and type I interferon production distinguish pathogenic and nonpathogenic AIDS virus infections

Abstract: Pathogenic HIV infections of humans and simian immunodeficiency virus (SIV) infections of rhesus macaques are characterized by generalized immune activation and progressive CD4(+) T cell depletion. In contrast, natural reservoir hosts for SIV, such as sooty mangabeys, do not progress to AIDS and show a lack of aberrant immune activation and preserved CD4(+) T cell populations, despite high levels of SIV replication. Here we show that sooty mangabeys have substantially reduced levels of innate immune system act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
348
8
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 341 publications
(384 citation statements)
references
References 60 publications
26
348
8
2
Order By: Relevance
“…To determine whether A3G was unique or merely representative of many innate responses contributing to protection, we further assessed natural killer (NK) cells, type I IFN, IFN regulatory factors, IFN-induced MxA (29), CXCL9, IL-1β, TNFα, and Granzyme B expression levels in the mesenteric lymph nodes (MLN) (Fig. S3), and did not observe significant differences among the groups, whereas type I IFN and TNFα 4 weeks after the last boost were up-regulated in the vaccinated group adjuvanted with TLR agonists alone, which had one of the highest VLs, consistent with the recent finding of a deleterious role played by type I IFN in mediating immune activation (30). In contrast, the combination of TLR agonists and IL-15 resulted in lower type I IFN, suggesting that IL-15 counteracts this effect by a mechanism that remains to be explored.…”
Section: Resultssupporting
confidence: 87%
“…To determine whether A3G was unique or merely representative of many innate responses contributing to protection, we further assessed natural killer (NK) cells, type I IFN, IFN regulatory factors, IFN-induced MxA (29), CXCL9, IL-1β, TNFα, and Granzyme B expression levels in the mesenteric lymph nodes (MLN) (Fig. S3), and did not observe significant differences among the groups, whereas type I IFN and TNFα 4 weeks after the last boost were up-regulated in the vaccinated group adjuvanted with TLR agonists alone, which had one of the highest VLs, consistent with the recent finding of a deleterious role played by type I IFN in mediating immune activation (30). In contrast, the combination of TLR agonists and IL-15 resulted in lower type I IFN, suggesting that IL-15 counteracts this effect by a mechanism that remains to be explored.…”
Section: Resultssupporting
confidence: 87%
“…39 Our data support the theory of activationinduced cell death being one mechanism of CD4 ϩ T-cell depletion in HIV infection, because susceptibility to pDC/TRAIL-mediated killing depends on the activation of CD4 ϩ T cells. This is underscored by our observation that the susceptibility of CD4 ϩ T cells depends on HIV viremia in vivo and/or activation of T cells in vitro.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, it has been suggested that HIV infection could promote PAH through indirect mechanisms and release of inflammatory mediators or growth factors. There is a chronic production of IFNa in patients with HIV infection [30,31] and an increased IFN expression correlates with HIV disease progression [32]. It is interesting to note that the proportion of patients with HIV co-infection in our study is higher than it is usually observed in patients with chronic HCV infection [33].…”
Section: Discussionmentioning
confidence: 42%